AUTHORITY CONFLICT OF THE COURTS IN ACEH: A CASE STUDY OF SETTLEMENT FOR CHILDREN SECLUSION IN CHILDREN PROTECTION - Teuku Muttaqin Mansur (Faculty of Law, Universitas Jenderal Soedirman, 2015)
This study is aims to discuss about Shari’a Courts, Adat Courts and The Juvenile Criminal Courts authority. And also to discuss about the concept of legal certainty, child protections and conflict jurisdiction of the courts cases involving Khalwat Moslem children in Aceh. These study adopted two approaches, namely normative and empirical approaches.The results showed that, all courts have jurisdiction to try cases of Khalwat Moslem children in Aceh. Therefore, there is legal uncertainty and conflict of jurisdiction courts. At the same time, resulting in the protection of the child is not fully guaranteed. Keywords: Cases of Khalwat Children, Child Protection, Conflict Jurisdiction of Courts, Legal Certainty